Matrix crack evolution in multi-directional composite laminates considering thickness effects. (2nd November 2018) - Jagannathan, N.; Gururaja, S.; Manjunatha, C.M.
Abstract : A probabilistic strength-based predictive model for matrix crack evolution in a multi-directional (MD) composite laminate considering thickness effect has been presented in the current work. Weibull distribution has been assumed for the in situ ply strength variation commonly observed in polymer composite laminates. The statistical parameters have been estimated from a master laminate. The crack density evolution has been simulated for cross-ply laminates containing varying thicknesses of and plies. The crack density evolution and associated stiffness degradation predictions have been compared with existing experimental values. The model has been extended to MD laminate containing plies of varying thicknesses to estimate the stiffness degradation under in-plane loading. The bounds on the stiffness have also been estimated. Good correlation is found to exist between the experimental data and simulation predictions.